2001
DOI: 10.1029/2000jc900143
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic properties derived from a simple cross‐shore sediment transport model

Abstract: Abstract. This paper builds on the now classical discussions by Bowen [1980] and Bailard [1981] on the applicability and implications of Bagnold's [1963] sediment transport model to nearshore profile modeling. We focus on the morphologic implications of both the strengths and weaknesses of Bagnold's model, isolating the transport terms that are well predicted (i.e., mean flow terms) from those that are not well predicted (i.e., transport due to correlations between flow and sediment load). We factor Bagnold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
87
2
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(92 citation statements)
references
References 33 publications
2
87
2
1
Order By: Relevance
“…This result confirms the validity of the implicit assumption often made in linear stability analyses that the 2DV morphological development of coastal systems is typically slower than the 2DH or 3D morphology, which is studied in this paper. This assumption is also validated by observations, see Ruessink et al (2000) and Plant et al (2001).…”
Section: Morphodynamic Equilibriumsupporting
confidence: 52%
“…This result confirms the validity of the implicit assumption often made in linear stability analyses that the 2DV morphological development of coastal systems is typically slower than the 2DH or 3D morphology, which is studied in this paper. This assumption is also validated by observations, see Ruessink et al (2000) and Plant et al (2001).…”
Section: Morphodynamic Equilibriumsupporting
confidence: 52%
“…Even though this simplified profile does not correspond exactly with any of the equilibrium profiles found in field observations or used in modelling (Dean 1991;Plant, Ruessink & Wijnberg 2000), it shares with them the main qualitative characteristic which is its concavity. In view of the fact that the investigation of equilibrium beach profiles is still under way (Plant et al 2000) and that we are interested in alongshore non-uniform features, this seems a reasonable choice. The vertical wall at the shoreline is introduced in order to avoid the complications of a moving shoreline and the dynamics of the swash zone that are expected to have little effect on the surf zone bars.…”
Section: Geometry and Boundary Conditionsmentioning
confidence: 93%
“…6 that the effect of memory on the cross-shore migration of the outer Gold Coast bar is negligible may advocate the use of MLPs for our future work on sandbar behavior. However, whether this conclusion also holds for the cross-shore migration of the inner bar (which is sheltered from the offshore waves by wave breaking on the outer bar and thus may respond differently to offshore wave forcing than the outer bar (Plant et al, 2001;Southgate & Möller, 2000)) and for the evolution of the abovementioned crescentic patterns remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…An example of modeling such temporal dependencies can be found in Wright, May, Short, and Green (1985), who use hydrodynamic forcings weighted over several days to provide for a measure of relaxation time in predicting the evolution of sandbar variability. Based on cross-shore sediment transport modeling, Plant, Ruessink, and Wijnberg (2001) also suggested that the response time of beach profiles is exceedingly long compared to the timescale of the variability of the offshore wave forcing. O'Hare and Huntley (2006) later on debated this suggestion, indicating that, while it may be true for quiescent wave conditions, the morphological timescale under storm conditions might be of the same order as the nearshore hydrodynamics.…”
Section: Introductionmentioning
confidence: 99%